Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Dager i Antarktis: om folk og forskning, og en ekspedisjon litt utenom det vanlige - Kristensen, Monica (Grøndahl Dreyer, 1993)
Keywords: Antarktis; ekspedisjoner

Regulation of parental effort in a long-lived seabird an experimental manipulation of the cost of reproduction in the antarctic petrel, Thalassoica antarctica - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Behavioral Ecology and Sociobiology, 1993)
The fitness of a parent in an altricial bird species is likely to be a function of the proportion of resources allocated to offspring production in relation to the amount spent on its own survival. Here we report an experiment on the Antarctic petrel in which we manipulated the costs of rearing an offspring by placing small lead loads on the legs of one parent. The bird could then either decrease its own body reserves or reduce the food load to the chick. The manipulated birds decreased their food load and increased the feeding interval, compared with unmanipulated birds. Consequently, the rate of chick loss increased. No significant difference was found between the body weights of experimental and control birds during the experiment.
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi; økologi